2008
DOI: 10.2353/ajpath.2008.080005
|View full text |Cite
|
Sign up to set email alerts
|

CGI-58 Is an α/β-Hydrolase within Lipid Transporting Lamellar Granules of Differentiated Keratinocytes

Abstract: CGI-58 is the causative molecule underlying DorfmanChanarin syndrome, a neutral lipid storage disease exhibiting apparent clinical features of ichthyosis. CGI-58, associated with triacylglycerol hydrolysis, has an ␣/␤-hydrolase fold and is also known as the ␣/␤-hydrolase domain-containing protein 5. The purpose of this study was to elucidate the function of CGI-58 and the pathogenic mechanisms of ichthyosis in Dorfman-Chanarin syndrome. Using an anti-CGI-58 antibody, we found CGI-58 to be expressed in the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…It is, however, unclear why permeability barrier remained intact in our patient, while the water holding capacity was markedly decreased in the involved lesions. Akiyama and coworkers recently demonstrated that CGI-58 knockdown reduced expression of keratinocyte differentiation markers including filaggrin [13], which plays an important role in retaining stratum corneum water.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is, however, unclear why permeability barrier remained intact in our patient, while the water holding capacity was markedly decreased in the involved lesions. Akiyama and coworkers recently demonstrated that CGI-58 knockdown reduced expression of keratinocyte differentiation markers including filaggrin [13], which plays an important role in retaining stratum corneum water.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated that the ultrastructure of DCS included abnormal lipid micro-inclusions within lamellar bodies and resulting lamellar/non-lamellar phase separation or clefts in the intercellular spaces of cornified layer [3,14,15]. Very recent study revealed that CGI-58 expression was increased during differentiation and localized in lamellar granules of keratinocytes and likely to be involved in barrier formation [13]. Given that TG is the content of lipid deposition in DCS, unsolved question is that the ultrastructural aberrancy in the epidermis is similar to other inherited, lipid storage diseases associated with ichthyosis, such as Refsum disease, Sjö gren-Larsson syndrome [15].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…8) are not competent for ATGL activation (1). CGI-58 mRNA is abundant in various tissues, including adipose tissue, liver, testis, neurons, muscle, and epidermis (1,9). Interestingly, mRNA expression levels of CGI-58 and ATGL do not correlate in the tissues tested (1, 10 -12).…”
mentioning
confidence: 99%
“…Furthermore, CGI-58 knockdown reduces the expression of keratinocyte differentiation markers in cultured human keratinocytes. 32) Thus, CGI-58 plays crucial roles in epidermal keratinocyte differentiation and LG lipid metabolism, thereby contributing to the formation of the skin's lipid barrier.…”
Section: Putative Functions Of Cgi-58 In Various Tissuesmentioning
confidence: 99%